Prevalence and risk factors of significant persistent pain symptoms after critical care illness: a prospective multicentric study - Alexandre Bourdiol; Vincent Legros; Fanny Vardon-Bounes; Thomas Rimmele; Paul Abraham; Clément Hoffmann; Claire Dahyot-Fizelier; Maud Jonas; Pierre Bouju; Cédric Cirenei; Yoann Launey; Gregoire Le Gac; et al. (Critical Care, 2023)
Abstract Background Prevalence, risk factors and medical management of persistent pain symptoms after critical care illness have not been thoroughly investigated. Methods We performed a prospective multicentric study in patients with an intensive care unit (ICU) length of stay ≥ 48 h. The primary outcome was the prevalence of significant persistent pain, defined as a numeric rating scale (NRS) ≥ 3, 3 months after admission. Secondary outcomes were the prevalence of symptoms compatible with neuropathic pain (ID-pain score > 3) and the risk factors of persistent pain. Results Eight hundred fourteen patients were included over a 10-month period in 26 centers. Patients had a mean age of 57 (± 17) years with a SAPS 2 score of 32 (± 16) (mean ± SD). The median ICU length of stay was 6 [4–12] days (median [interquartile]). At 3 months, the median intensity of pain symptoms was 2 [1–5] in the entire population, and 388 (47.7%) patients had significant pain. In this group, 34 (8.7%) patients had symptoms compatible with neuropathic pain. Female (Odds Ratio 1.5 95% CI [1.1–2.1]), prior use of anti-depressive agents (OR 2.2 95% CI [1.3–4]), prone positioning (OR 3 95% CI [1.4–6.4]) and the presence of pain symptoms on ICU discharge (NRS ≥ 3) (OR 2.4 95% CI [1.7–3.4]) were risk factors of persistent pain. Compared with sepsis, patients admitted for trauma (non neuro) (OR 3.5 95% CI [2.1–6]) were particularly at risk of persistent pain. Only 35 (11.3%) patients had specialist pain management by 3 months. Conclusions Persistent pain symptoms were frequent in critical illness survivors and specialized management remained infrequent. Innovative approaches must be developed in the ICU to minimize the consequences of pain. Trial registration. NCT04817696. Registered March 26, 2021.